Features of Auxiliaries That Enable Native Chemical Ligation beyond Glycine and Cleavage via Radical Fragmentation. Issue 14 (12th February 2018) - Loibl, Simon F.; Dallmann, Andre; Hennig, Kathleen; Juds, Carmen; Seitz, Oliver
Abstract: Native chemical ligation (NCL) is an invaluable tool in the total chemical synthesis of proteins. Ligation auxiliaries overcome the requirement for cysteine. However, the reported auxiliaries remained limited to glycine‐containing ligation sites and the acidic conditions applied for cleavage of the typically applied N ‐benzyl‐type linkages promote side reactions. With the aim to improve upon both ligation and cleavage, we systematically investigated alternative ligation scaffolds that challenge the N ‐benzyl dogma. The study revealed that auxiliary‐mediated peptide couplings are fastest when the ligation proceeds via 5‐membered rather than 6‐membered rings. Substituents in α‐position of the amine shall be avoided. We observed, perhaps surprisingly, that additional β‐substituents accelerated the ligation conferred by the β‐mercaptoethyl scaffold. We also describe a potentially general means to remove ligation auxiliaries by treatment with an aqueous solution of triscarboxyethylphosphine (TCEP) and morpholine at pH 8.5. NMR analysis of a 13 C‐labeled auxiliary showed that cleavage most likely proceeds through a radical‐triggered oxidative fragmentation. High ligation rates provided by β‐substituted 2‐mercaptoethyl scaffolds, their facile introduction as well as the mildness of the cleavage reaction are attractive features for protein synthesis beyond cysteine and glycine ligation sites. Abstract : Efficient peptide ligation auxiliaries have a β‐mercaptoethyl scaffold and avoid substituent in α‐position to the amine. Surprisingly, β‐substituents accelerate ligation reactions. All presented auxiliaries can be removed under mild‐basic conditions. NMR analysis of a 13 C‐labelled auxiliary indicated that auxiliary cleavage most likely proceeds through a radical oxidation‐fragmentation cascade.